Context-based Access Control and Attack Modelling and Analysis - Walter, Maximilian (The Karlsruhe Series on Software Design and Quality, 2024)
This work introduces architectural security analyses for detecting access violations and attack paths in software architectures. It integrates access control policies and vulnerabilities, often analyzed separately, into a unified approach using software architecture models. Contributions include metamodels for access control and vulnerabilities, scenario-based analysis, and two attack analyses. Evaluation demonstrates high accuracy in identifying issues for secure system development.